Automatic or controlled: How does disbelief in free will influence cognitive functioning?. (15th June 2022) - Katzir, Maayan; Genschow, Oliver
Abstract: Most people believe in free will. Past research has indicated that reducing this belief has numerous downstream consequences including everyday outcomes as well as neural and cognitive correlates associated with a reduction of self‐control. However, the exact mechanisms through which a reduction in free will belief affects self‐control are still a matter of investigation. In the present registered report, we used a task switching paradigm to examine whether reducing belief in free will makes people less controlled or whether it enhances their reliance on automatic impulses. Using Bayesian sequential analysis, we failed to conceptually replicate the previous link between free will belief and cognitive control. Our registered report plan mostly accumulated substantial evidence supporting the null hypothesis. That is, diminished belief in free will does neither impact control nor automaticity. Theoretical implications of this finding are discussed.